Pandangan Hukum Islam Terhadap Akad Pernikahan Berulang - Oktavia Oktavia (CV Rewang Rencang, 2025)
Marriage is an important thing in Islam which is regulated by strict legal principles. However, in practice, there are several traditions that involve repeated marriage contracts such as those carried out when there is a problem in the family that occurs continuously, such as there is something strange in the hearts of each partner then repeating the contract or renewing the marriage with the same partner without divorce. The formulation of the problem that occurs in this study is, how is the practice of the tradition of repeated marriage contracts? And what is the view of Islamic law on the tradition of repeated marriage contracts? This research method uses a field research method with this research being descriptive qualitative with primary data sources (obtained directly from the field) and secondary data (books, journals, etc.) and data collection methods, namely by observation, interviews and documentation. while data analysis is carried out qualitatively with an inductive thinking method. The results of this study conclude that the tradition of repeated marriage contracts is a common practice in society. This practice is carried out as an effort to renew the bonds of marriage with the aim of maintaining harmony and the integrity of the household. The process of repeated marriage contracts involves several elements such as the groom, bride, dowry, guardian nashab, witnesses, and the pronunciation of ijab and qabul. Although it does not require an official record from the KUA, the process still follows the rules that have been determined. The views of Islamic law regarding this matter are divided into two, some allow it as long as it is to maintain family harmony because maintaining family harmony is an obligation. Some prohibit it because it is considered that the second contract is considered to cancel the first contract.